Football, Tragedy and Social Solidarity Movement - Shendy Marshanda Putri (Political Sciences Program Study, 2024)
This study discusses social solidarity movement in the case football tragedy in Kanjuruhan. Kanjuruhan tragedy occurred on October 1, 2022 in Malang City. It killed 219 spectators and triggered a social movement involving football supporters, human rights activists, and civil society organizations. The main issue raised in this research is how the social movement emerged after the tragedy can encourage stadium security reform and the accountability of the actors involved. This research uses a qualitative approach. The theory used is Charles Tilly's social movement theory that views social movements as organized collective actions with political or social goals. In addition, resource mobilization theory is also applied to understand how supporters groups organize themselves through social media and social movement. The findings show that the social movement after the Kanjuruhan Tragedy is able to build a strong solidarity between supporters groups that are usually divided due to rivalry. And, this movement succeeded in pressuring the government to create a collaborative independent fact-finding team (TGIPF). Despite the progress in raising public awareness and discussing football management reformed, the social movement faces any obstacles in enforcing transparent accountability and deep institutional reformation. These findings underscore the importance of collective action and resource mobilization in driving social change.